1986
DOI: 10.1063/1.450901
|View full text |Cite
|
Sign up to set email alerts
|

The scattering matrix for randomly oriented particles

Abstract: An efficient numerical method is derived for evaluation of the scattering properties of randomly distributed particles described by the coupled dipole approximation. An exact analytic average for these properties is also derived. All elements of the scattering matrix for a collection of randomly oriented particles can be obtained by either method. The results are applicable to model calculations of the scattering matrix for realistic particles. The analytic average also allows qualitative interpretation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Singham et al [136] noted that the set of problems described above is physically equivalent to a fixed orientation of the particle and different incident and scattering directions. The latter are determined by transformation of the laboratory reference frame to the reference frame associated with the particle.…”
Section: Orientation Averaging and Repeated Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Singham et al [136] noted that the set of problems described above is physically equivalent to a fixed orientation of the particle and different incident and scattering directions. The latter are determined by transformation of the laboratory reference frame to the reference frame associated with the particle.…”
Section: Orientation Averaging and Repeated Calculationsmentioning
confidence: 99%
“…If or its LU decomposition is obtained [75,136], a single solution for any right part y can be obtained in n 1 −…”
Section: Orientation Averaging and Repeated Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we have provided the rigorous (and long overdue) justification of the main premises implicit in Refs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and numerous related publications. The laboratory, Oxyz, and particle, Ox′y′z′, reference frames having a common origin.…”
mentioning
confidence: 99%
“…They applied the coupled dipole approximation to a variety of structures for single particles 41 and for an orientation average. 42 They showed that a helix modelled by spherical or prolate spheroidal subunits is equivalent as long as the thickness of the subunits are the same and Maxwell-Garnett theory 40 is used to determine the polarizability of the dipole representing the subunit. 43 In the same publication this group did a preliminary investigation of the necessity of including dipolar interactions.…”
mentioning
confidence: 99%